APPLICATION DESIGN FOR EVALUATION OF THE EFFECT OF RESEARCH VARIABLES AND THEIR IMPACT USING PEARSON PRODUCT MOMENT AND SIMPLE LINEAR REGRESSION - Romanus Damanik; Alex Rikki; Parasian D.P Silitonga (Sean Institute, 2022)
Research is a process to solve problems. To solve existing problems, researchers must process data related to the problem to be solved. Data processing can be done using the SPSS application program, but the results obtained are still in the form of numerical values ​​that must be concluded with sentences. To speed up data processing and determine conclusions, it is necessary to build an application for evaluating the influence of research variables and their impacts to help researchers, especially in the social field, to speed up in determining conclusions on evaluating the influence of research variables and their effects using the Pearson product moment method and simple linear regression. With the application that was built, the correlation coefficient of monthly money on student GPA is 0.0603 and the regression equation Y= 3.1319 + 0.0084 X , where there is an effect of student monthly money on student GPA of one hundred thousand rupiah, then the student's IP will increase by 0.0084